FORMATION OF LOGICAL CULTURE OF SENIOR STUDENTS IN THE STUDY OF INFORMATICS - Lavreshyna, H.Yu. (Educational Dimension, 2004)
In this article opened the system of educational exercises on development of logic culture of senior pupils at lessons of computer science.